2023
DOI: 10.1177/17562848231167858
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and type of adverse events in patients taking vonoprazan: A systematic review and meta-analysis

Abstract: Background: Vonoprazan, a novel acid-suppressive drug, is non-inferior to proton pump inhibitors (PPIs) for the management of gastric acid-related diseases. However, the safety of vonoprazan has not been systematically evaluated yet. Objectives: To elucidate the incidence and type of adverse events (AEs) in patients taking vonoprazan. Design: Systematic review and meta-analysis. Data sources and methods: PubMed, EMBASE, and Cochrane Library databases were searched for all studies reporting the safety of vonopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 99 publications
1
2
0
Order By: Relevance
“…Serious adverse events unrelated to the study drugs including acute pancreatitis, subcutaneous abscess, and muscular weakness, among others. This result was consistent with the previously meta-analysis about adverse events of vonoprazan ( Xu et al, 2023 ). Further investigation is needed to determine whether these events are indeed related to the use of P-CABs.…”
Section: Disscussionsupporting
confidence: 93%
“…Serious adverse events unrelated to the study drugs including acute pancreatitis, subcutaneous abscess, and muscular weakness, among others. This result was consistent with the previously meta-analysis about adverse events of vonoprazan ( Xu et al, 2023 ). Further investigation is needed to determine whether these events are indeed related to the use of P-CABs.…”
Section: Disscussionsupporting
confidence: 93%
“…Additionally, a meta-analysis on acid-related diseases also found that the incidence of adverse events in patients with duodenal ulcers treated with vonoprazan was significantly higher than that with PPIs [ 90 ]. Another study evaluated the safety of vonoprazan in various indications, and the results showed that patients with peptic ulcers had a higher rate of adverse events than other acid-related diseases such as gastroesophageal reflux and H. pylori infection [ 91 ]. This may be due to the fact that peptic ulcers are more complex and require longer treatment than other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that peptic ulcers are more complex and require longer treatment than other diseases. The most common adverse events associated with vonoprazan include increased serum gastrin levels, followed by increased pepsinogen I levels, nasopharyngitis, bloating, loose stools, and so on [ 91 , 92 ]. In addition, studies have reported that vonoprazan can affect human gut microbiota [ 93 ].…”
Section: Discussionmentioning
confidence: 99%